The Role of a Code of Ethics in Athletic Academic Counseling - Mayo, Ann M. (My University, 1986)
The following article offers an argument for the development of a code of ethics for the profession of athletic academic counseling. The effects of recent scandals in athletics and the need for the establishment of athletic academic advising as a profession, call for an examination of the development of a code of ethics. The role of a code of ethics, as well as the possible dysfunctions of such a code are examined.
Keywords: ethics